THE QASIDA GENRE IN ARABIC AND UZBEK LITERATURE: A COMPARATIVE STUDY OF SIMILARITIES (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2026)
The qasida is one of the oldest and most influential poetic genres in Eastern literature, particularly in Arabic and later in Persian and Turkic literary traditions, including Uzbek literature. Originating in pre-Islamic Arabia, the qasida developed as a sophisticated poetic form that served various social, political, and aesthetic purposes. This article aims to examine the qasida genre in both Arabic and Uzbek literature, focusing on its origins, structural features, thematic scope, and artistic functions. Through a comparative analysis, the study highlights the shared characteristics of the qasida in these two literary traditions and explains how Arabic classical poetry significantly influenced the formation and development of the qasida in Uzbek literature. The article also emphasizes the role of the qasida as a medium of praise, moral reflection, and cultural expression.